Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/cvr/cvaa066
|View full text |Cite
|
Sign up to set email alerts
|

Pim1 maintains telomere length in mouse cardiomyocytes by inhibiting TGFβ signalling

Abstract: Aims Telomere attrition in cardiomyocytes is associated with decreased contractility, cellular senescence, and up-regulation of proapoptotic transcription factors. Pim1 is a cardioprotective kinase that antagonizes the aging phenotype of cardiomyocytes and delays cellular senescence by maintaining telomere length, but the mechanism remains unknown. Another pathway responsible for regulating telomere length is the transforming growth factor beta (TGFβ) signalling pathway where inhibiting TGFβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Previous reports indicated that the phosphorylated SMAD3 is elevated markedly in the lung of G3 TERC –/– mice ( Liu et al, 2018 ), and SMAD3 binds directly to the promoter of TERT gene and induces TERT gene repression ( Li and Liu, 2007 ; Cassar et al, 2010 ). By inhibiting phosphorylation of SMAD2/3, which prevents repression of TERT, Pim1 maintains telomere lengths in cardiomyocytes ( Ebeid et al, 2021 ). Our results indicate that GDF11 maintains telomere length in Neuro 2a cells, unlike TGF-β which shortens telomere in cancer cells ( Li and Liu, 2007 ; Cassar et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that the phosphorylated SMAD3 is elevated markedly in the lung of G3 TERC –/– mice ( Liu et al, 2018 ), and SMAD3 binds directly to the promoter of TERT gene and induces TERT gene repression ( Li and Liu, 2007 ; Cassar et al, 2010 ). By inhibiting phosphorylation of SMAD2/3, which prevents repression of TERT, Pim1 maintains telomere lengths in cardiomyocytes ( Ebeid et al, 2021 ). Our results indicate that GDF11 maintains telomere length in Neuro 2a cells, unlike TGF-β which shortens telomere in cancer cells ( Li and Liu, 2007 ; Cassar et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decades of cardioprotective signal transduction studies have produced an intricate web of relationships between mediators of cardiomyocyte survival. Our group were pioneers in establishing PIM1-mediated cardioprotection in over a decade of studies [ 8 , 9 , 16 , 29 , 30 , 33 , 34 , 35 ], which was subsequently reinforced by studies from other researchers [ 7 , 10 , 36 , 37 ]. Similarly, cardioprotection is also conferred by c-Kit activity [ 17 , 32 , 38 ], with c-Kit biology inextricably linked to myocardial homeostasis [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, PIM1 upregulates c-Kit protein expression to promote protection in cardiomyocytes, consistent with cumulative evidence of cardioprotection as well as preservation of a more “youthful” phenotype mediated by PIM1 overexpression [ 9 , 29 , 34 , 53 ]. Reinforcement of c-Kit activity by PIM1 could account for the ability of PIM1 to antagonize cellular senescence [ 33 , 53 ] and serve as the basis for future studies. Mechanistic understanding of PIM1-mediated cardioprotection could provide valuable information towards the protection of cardiomyocytes to promote cardiac repair.…”
Section: Discussionmentioning
confidence: 99%
“…CMs belong to postmitotic cells, and biomechanical stress, oxidative stress, and inflammation can also cause telomere attrition, eventually leading to cellular senescence [ 123 , 124 ]. Hyperglycemia accelerates senescence in CMs by inducing various cellular stressors, such as oxidative stress, DNA damage, and telomere erosion, which is a well-accepted reason for the increased incidence of cardiovascular disease in diabetic individuals [ 118 ].…”
Section: Cellular Senescence Affects Cardiac Regeneration and Repairmentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) plays a role in reducing cellular senescence in the process of MI and cardiac aging [ 125 ]. Ebeid DE et al found that PIM1 is a myocardial protective kinase that delays cellular senescence by maintaining the telomere length [ 123 ]. Rb1 and Meis homeobox 2 (Meis2) is a set of cell cycle inhibitors [ 126 ].…”
Section: Cellular Senescence Affects Cardiac Regeneration and Repairmentioning
confidence: 99%